Leading the Teacher Induction and Mentoring Program. - Sweeny, Barry W. (SAGE Publications, 2007)
"A must-read for anyone interested in ensuring the ongoing effectiveness of teacher induction and mentoring. Sweeny mentors the reader by sharing details from his two decades of developing and leading high-impact mentoring programs. I've improved my own effectiveness by employing these insightful strategies."